Deaf Students' Challenges in Learning English: A Literature Review - Nugroho, Fajar Ainun; Lintangsari, Alies Poetri (Indonesian Journal of Disability Studies, 2022)
In language learning, the understanding towards the language usage which is appropriate with the grammatical rules is an important thing, because most of the students’ tasks are dealing with writing, especially writing a scientific paper. In the writing process, Deaf students sometimes struggles with the writing issues. One of their writing issues is the difficulties in understanding the concept of a language which is suitable with the grammar rules, word order, etc. The type of this research is Literature review research, and the method or structure used in this research is Narrative literature review with chronological order. This research mostly discussing the difficulties and challenges faced by Deaf student and the teacher in the teaching and learning English as a foreign language. The data gained in this research is using the review from 10 journal articles. Thus, the goal of this research is to identify the challenge of Deaf students in learning English, especially at the university level.